2011
DOI: 10.1158/1541-7786.mcr-11-0351
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Multidomain Human p53 Tetramer Bound to the Natural CDKN1A (p21) p53-Response Element

Abstract: The p53 tumor suppressor protein is a sequence-specific DNA-binding transcription factor. Structures of p53 bound to DNA have been described, but, so far, no structure has been determined of p53 bound to a natural p53-response element. We describe here the structure of a human p53 homotetramer encompassing both the DNA-binding and homo-oligomerization domains in complex with the natural p53-response element present upstream of the promoter of the CDKN1A (p21) gene. Similar to our previously described structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
88
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 31 publications
1
88
0
Order By: Relevance
“…3A). REs with 2-bp spacers or shorter allow the formation of tetramers, as in crystal forms 1 and 2 or in reported structures of p53 and p63 (17)(18)(19)(20)(21)(22)(23). When p73 DBD binds to DNA with spacers larger than 2 bp, it does not form tetramers and the inability to tetramerize might explain the lack of p73β transactivation observed in the yeast-based assay.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…3A). REs with 2-bp spacers or shorter allow the formation of tetramers, as in crystal forms 1 and 2 or in reported structures of p53 and p63 (17)(18)(19)(20)(21)(22)(23). When p73 DBD binds to DNA with spacers larger than 2 bp, it does not form tetramers and the inability to tetramerize might explain the lack of p73β transactivation observed in the yeast-based assay.…”
Section: Discussionmentioning
confidence: 92%
“…When p73 DBD binds to DNA with spacers larger than 2 bp, it does not form tetramers and the inability to tetramerize might explain the lack of p73β transactivation observed in the yeast-based assay. Regarding the DNA conformation, some studies on p53 have shown DNA bending (17,18,20), whereas others have not (19,21,23). In the case of p73 DBDs, dimers bind to an undisturbed B-DNA half-site RE and bending in the half-sites is not observed; on the other hand, when two oligonucleotides stack to form the 20-bp RE with 1-or 2-bp spacers, the p73 DBD tetramer is still able to recognize both half-site REs and compensates the insertions by unwinding the DNA 30°and 60°, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DBD is a 200-amino acid immunoglobulin-like domain with two ␤-sheets packed as a ␤-sandwich (16). Several structures of the members of the p53 transcription factor family in complex with DNA have been solved (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The DBD binds as a tetramer to response elements (REs), with each monomer recognizing a 5-bp quartersite of the 20-bp full-site RE.…”
mentioning
confidence: 99%
“…How full-length wild-type human p53 associates with its binding targets remains inconclusive, in large part due to the inherent structural plasticity of the protein at its N-terminal and C-terminal domains (Okorokov et al 2006;Emamzadah et al 2011;Melero et al 2011;Pham et al 2012). For instance, p53, along with other potent transcriptional activators (e.g., VP16), contains intrinsically disordered regions that fold upon interaction with different partners (Triezenberg 1995;Dyson and Wright 2005;Jonker et al 2005;Lee et al 2009;Park et al 2011).…”
Section: Discussionmentioning
confidence: 99%